Síntese e caracterização elétrica de filmes varistores à base de 'SN''O IND.2' modificados superficialmente por difusão 'CR POT.3+' na região do contorno de grão - Lustosa, Glauco Meireles Mascarenhas Morandi [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The present work was studied obtaining nanoparticles of the system (98,95)SnO2(1,0)ZnO(0,05)Nb2O5 by Pechini method (polymeric precursor method) and the preparation of varistors films of these particles. The powder obtained was characterized by X-Ray Diffraction, Scanning electron microscopy and N2 adsorption. The films of nanoparticles were obtained by deposition on Si (100)/TiO2 (10.000 A°)/Ti (200 A°)/Pt (1500 A°) substrate with 356-406 of thickness, by electrophoretic technique, using stable suspension of this powder. The films were sintered in the microwave oven for temperatures up to 1000 °C and time up to 40 minutes, in order to form and growth of grains. After sintering and characterization SEM, was deposited a layer of Cr3+ ions by electrophoresis on the surface of the film and submitted to heat treatment of 900 and 1000 ° C for 5, 10 and 15 minutes for purposes of diffusion of cations in the grain boundaries. The Cr+3 is responsible for increasing the coefficient of nonlinearity in varistor system based on SnO2, main characteristic required to obtain varistors. This addition allows to control, through the diffusion by heat treatment, the resistivity, breakdown voltage and nonlinearity coefficient in ceramic films based on SnO2 order to use as varistors. After deposition of ions Cr3+ and heat treatment, the films were electrically characterized by analyzing a direct current to the determination of curves V vs I (voltage applied as a function of electrical current) and curves ln(J/T²) vs E1/2, and characterization alternating current (impedance spectroscopy). From the V vs I curves was possible to obtain the coefficient of nonlinearity, breakdown voltage and leakage current. The parameters of the potential barrier formed at grain boundary region were calculated after analysis of the curves ln(J/T²) vs E1/2 obtained by the V vs I measurements as a function of temperature. The films showed nonlinear coefficient (α)...

No presente trabalho foi estudada a obtenção de nanopartículas do sistema (98,95)SnO2(1,0)ZnO(0,05)Nb2O5 através do Método Pechini (método dos precursores poliméricos) e a preparação de filmes varistores destas partículas. O pó obtido foi caracterizado por Difração de Raios X, Microscopia eletrônica de Varredura e adsorção de N2. Os filmes das nanopartículas foram obtidos por deposição em substrato de Si (100)/TiO2 (10.000 A°)/Ti (200 A°)/Pt (1500 A°), com espessura 356-406 nm, através da técnica de eletroforese, utilizando suspensão etílica estável deste pó. Os filmes foram sinterizados em forno microondas por temperaturas de até 1000 °C e patamar de até 40 minutos visando à formação e o crescimento dos grãos. Após a sinterização e caracterização por MEV_FEG, foi depositada uma película de íons Cr3+ através da eletroforese na superfície dos filmes e submetidos aos tratamentos térmicos de 900 e 1000 °C por 5, 10 e 15 minutos para fins de difusão dos cátions nos contornos de grãos. O Cr+3 é responsável pelo aumento do coeficiente de não-linearidade no sistema varistor a base de SnO2, característica principal desejada na obtenção de varistores. Esta adição permite controlar, através da difusão por tratamento térmico, a resistividade, a tensão de ruptura e coeficiente de não linearidade em filmes cerâmicos à base de SnO2 visando a aplicação como varistores. Após deposição dos íons de Cr3+ e do tratamento térmico, os filmes foram caracterizados eletricamente através da análise em corrente contínua, para a determinação das curvas V vs I (tensão aplicada em função da corrente elétrica) e das curvas ln(J/T²) vs E1/2, e caracterização em corrente alternada (espectroscopia de impedância). A partir das curvas V vs I foi possível obter valores do coeficiente de não-linearidade, campo elétrico de ruptura e corrente de fuga. Os parâmetros da barreira de potencial formada...
Keywords: Bioquímica; Sinterização; Eletroforese; Cereais; Cations; Biochemistry